Peranan Camat Sebagai Koordinator dalam Penyelenggaraan Pemerintahan di Kecamatan Baranti Kabupaten Sidenreng Rappang - Andi Nilwana (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2012)
Playing the role of government at subdistrict region involves anumber of instances that play their own jobs and functions.Therefore a good coordination is also required to preventmisfunction get in the way.This research is done to determine the role of coordinator of thesubdistrict leader in order to accomplish the job, and to determinethe influencing factors that get into play. So that this research wouldgive a positive contribution in subdistrict government particularlyand generally the whole country.The methods used in collecting data are (1) observation, (2)interview, (3) questionaire, and (4) literature study. Those data thenanalyzed using frequency table and percentage.The population of this research is 30 people, all accounted asresearch samples. The result shows percentage of 85% thatsubdistrict leader coordinates well in Baranti subdistrict of Sidrapregency. That means a good coordination between subdistrict andall sub-intances involved, and a positive contribution inaccomplishing all jobs and duties at Baranti subdistrict government